The Effect of Leadership, Organizational Culture and Work Disicpline on Employee Performance (Case Study in Central Java Disporapar) - Isnaningtyas Febrianti; Sri Isnowati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research was conducted at DISPORAPAR JATENG. The purpose of this research is to analyze the Influence of Leadership, Organizational Culture and Work Discipline. This type of research is quantitative by distributing questionnaires, in collecting data using porpusive sampling technique with a sample of 89 respondents. The problems that occur at the DISPORAPAR JATENG in leadership are still not firm, the organizational culture that is seen to still behave as it pleases and work discipline there are still some employees who do not obey the rules. The tests used in this study are validity test, reliability test, multiple regression analysis, determinant coefficient, f test (Simultaneous) and t test (partial). The results of this study indicate that leadership, organizational culture and work discipline simultaneously have a significant influence on employee performance. The results of the coefficient of determination show that the value of R2 is 0.916, meaning that the variables of leadership, organizational culture and work discipline are able to explain 91.6 of the performance of the DISPORAPAR JATENG employees. The remaining 8.4 is influenced by variables that are not observed.